Nomogram of Thai fetal maxillary bone length at 11-13+6 weeks of gestation - Sukanya Chaiyarach (Thai Journal of Obstetrics and Gynaecology, 2012)
Objectives: To evaluate fetal maxillary bone length during 11-13+6 weeks of gestation in Thai population.Material and Method: Thai women with singleton pregnancy between 11-13+6 weeks of gestation were enrolled. Fetal crown-rump length (CRL), and maxillary bone length (MAX) were measured. A nomogram of MAX was derived. The best fit equations between MAX and CRL, MAX and gestational age (GA) were constructed. The equations were compared with other reported.Results: A total of 186 Thai pregnant women were recruited. The mean gestational age was 12+3 weeks (SD= 6 days). Curve estimation analysis demonstrated a linear relationship between MAX and CRL and GA. A comparison of MAX using the equation derived from a Thai population and the equation derived from a Chinese population demonstrated a significant difference between the two ethnicities (p<0.001).Conclusion: The nomogram of fetal MAX in the first trimester in Thai population was constructed. The fetal MAX in a Thai population appears to be different from Chinese population.